Legal Liability to Volunteers in Testing New Drugs - Bowker, W. F. (1963)
Scientists test new drugs by giving them to volunteers. In spite of every precaution, the drug may harm the volunteer. Under Canadian law, can he recover damages against any of the persons connected with the test? He cannot succeed against the scientist if the latter had made complete disclosure of the risks and had then obtained the volunteer's free consent. Where the subject of a test is a child or one of unsound mind, the guardian's consent probably does not protect the scientist from a possible claim by the subject. Where a married woman is a volunteer, her husband's consent is unnecessary. The volunteer cannot succeed against his family physician who referred him to the scientist unless the physician took an active part in an experiment that was conducted negligently or without a proper consent. The volunteer cannot succeed against the maker unless he has negligently prepared the drug or given misleading information.